Anti-platelet Factor 4 Antibody-Mediated Disorders: An Updated Narrative Review - Napolitano, Angela; Spiezia, Luca; Biolo, Marta; Radu, Claudia Maria; Toffanin, Serena; Campello, Elena; Simioni, Paolo (Seminars in Thrombosis and Hemostasis, 2025)
Anti-platelet factor 4 (PF4) antibody-mediated disorders are a heterogeneous group of diseases characterized by the presence of highly pathogenic immunoglobulins G directed against PF4 and/or PF4/heparin complexes. These antibodies are able to activate platelets, neutrophils, and monocytes, thus resulting in thrombocytopenia and a hypercoagulable state. Five different forms of anti-PF4 antibody-mediated disorders have been identified: (1) classic heparin-induced thrombocytopenia (HIT) mediated by heparin and certain polyanionic drugs; (2) autoimmune HIT characterized by the presence of anti-PFA/polyanion antibodies that can strongly activate platelets even in the absence of heparin; (3) spontaneous HIT characterized by thrombocytopenia and thrombosis without proximate exposure to heparin, with two subtypes: (a) post-total knee arthroplasty and cardiac surgery using cardiopulmonary bypass or extracorporeal membrane oxygenation and (b) postinfections; (4) vaccine-induced immune thrombotic thrombocytopenia (VITT) characterized by thrombocytopenia, arterial and venous thrombosis, or secondary hemorrhage after receiving adenoviral vector vaccines for coronavirus disease 2019; (5) VITT-like disorders triggered by adenoviral infections. Although extremely rare and largely unknown, there has been growing interest in the VITT syndrome in recent years due to its clinical relevance. Timely detection of these antibodies is crucial for the diagnosis and treatment of anti-PF4 antibody-mediated disorders, via anti-PF4 antibody immunoassays using several antibody capture systems (e.g., enzyme-linked immunosorbent assay-based, particle gel, turbidimetry) and functional assays (e.g., serotonin release assay or heparin-induced platelet activation). We aimed to present the latest on laboratory findings, clinical characteristics, and therapeutic approaches for anti-PF4 antibody-mediated disorders.
Keywords: anti-PF4 antibody-mediated disorders; heparin-induced thrombocytopenia; VITT